Microfluidic platforms for advanced risk assessments of nanomaterials. Issue 3 (May 2015) - Mahto, Sanjeev Kumar; Charwat, Verena; Ertl, Peter; Rothen-Rutishauser, Barbara; Rhee, Seog Woo; Sznitman, Josué
Abstract In the past few years, promising efforts to utilize microfabrication-based technologies have laid the foundation for developing advanced, and importantly more physiologically-realistic, microfluidic methods for risk assessment of engineered nanomaterials (ENMs). In the present review, we discuss the wave of recent developments using microfluidic-based in vitro models and platforms for nanotoxicological assays, such as determination of cell viability, cellular dose, oxidative stress and nuclear damage. Here, we specifically highlight the tangible advantages of microfluidic devices in providing promising tools to tackle many of the current and ongoing challenges faced with traditional toxicology assays. Most importantly, microfluidic technology not only allows to recreate physiologically-relevant in vitro models for nanotoxicity examinations, but also provides platforms that deliver an attractive strategy towards improved control over applied ENM doses. In a final step, we present examples of state-of-the-art microfluidic platforms for in vitro assessment of potential adverse ENM effects.